Decision Support System to Determine the Number of Production Tofu using the Fuzzy Sugeno Method (Case Study: Home Industries Tofu in Seyegan District) - Indrianingsih, Yuliani (SENATIK STT Adisutjipto, 2018)
The production process is a way to increase the usefulness of an item and service using existing production factors. The decision making process to determine the amount of production, especially in the business world contains risks. It needs to be supported by careful calculations so that the risk of loss can be avoided. Industri associations tofu "Waluyo" in Seyegan who still determines the amount of production manually. From the above problems a Decision Support System (DSS) was made using Sugeno's fuzzy method. In this DSS there are three variables modeled, namely, inventory variables, demand variables and production variables. The demand variable consists of two fuzzy sets, the inventory variable consists of two fuzzy sets and 4 rules which are the production rules used by Industry associations tofu "Waluyo" in determining the amount of production. Based on the acuracy   test using the MAPE (Mean Absolute Percentage Error) method obtained a value of 5,3069% or below the error rate of 10%. So this system can be applied in determining the amount of tofu production in the tofu industri community in Seyegan.